2013
DOI: 10.1016/j.apenergy.2013.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Summer comfort in a low-inertia building with a new free-cooling system

Abstract: Wood-framed buildings are considered to have low energy consumption since their construction mode generally gives high U-values and limited thermal bridges. Although the construction mode results in low heating consumption, the lack of storage capacity in the internal walls makes passive cooling designs such as night ventilation inappropriate. Consequently, the interior is subject to considerable temperature swings and higher temperatures than those of buildings with more massive internal surfaces. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The general idea presented in this paper is to provide the building http with stocks having an inertial potential enable to exploit the freshness of the night when available in order to smooth the internal temperature during summer. Some systems using the inertia of some materials coupled with ventilation have been studied in [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general idea presented in this paper is to provide the building http with stocks having an inertial potential enable to exploit the freshness of the night when available in order to smooth the internal temperature during summer. Some systems using the inertia of some materials coupled with ventilation have been studied in [1].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial discretization scheme in the PCM with airflow in x direction 1. For interpretation of color inFig.…”
mentioning
confidence: 99%
“…The latent heat transfer is approximately an isothermal process as PCMs absorb and discharge heat at almost a constant temperature or within a narrow temperature range which is more applicable for maintaining thermal comfort compared to SHS [46,47]. Another important advantage of LHS is their easy integration where other SHS substances are difficult to be installed particularly in existing buildings and lightweight structures [48]. This is because PCMs are capable of enhancing the mass effect with much lighter weight and volume estimated at 5-14 times compared to conventional SHS systems which require a large space for accumulator accommodation [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…As a main result, the diffusive heat transfer coefficient and thereby the global air/soil heat transfer coefficient are derived as a function of the available soil layer, which leads the way to the design rules developed in this article. As a second result it is also shown that, for a particularly thin layer submitted to adiabatic boundary condition, it is possible to completely phaseshift the periodic input while barely dampening its amplitude, a phenomenon that lead to the development of a new passive cooling technique [21,22], which will not be treated in this article.…”
Section: Analytical Modelsmentioning
confidence: 99%